2019
DOI: 10.1002/ange.201907971
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time In‐Situ Monitoring of a Tunable Pentapeptide Gel–Crystal Transition

Abstract: Supramolecular gels often become destabilizedb y the transition of the gelator into amore stable crystalline phase, but often the long timescale and sporadic localization of the crystalline phase preclude ap ersistent observation of this process.W epresent apentapeptide gel-crystal phase transition amenable for continuous visualization and quantification by common microscopic methods,a llowing the extraction of kinetics and visualization of the dynamics of the transition. Using optical microscopya nd microrheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…As shown by some models [ 11 ], even if the molecules are achiral it can assemble in a chiral way, if the molecules pack in a chiral way. We have shown that the tubes are metastable, and they transform into crystals after 28 h. Such transformations in organogels, have been observed for other gelators [ 25 , 26 ]. Given the shape of the aggregates, it is relevant to compare HUB-4 also with lipid compounds self-assembling in metastable nanotubes [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…As shown by some models [ 11 ], even if the molecules are achiral it can assemble in a chiral way, if the molecules pack in a chiral way. We have shown that the tubes are metastable, and they transform into crystals after 28 h. Such transformations in organogels, have been observed for other gelators [ 25 , 26 ]. Given the shape of the aggregates, it is relevant to compare HUB-4 also with lipid compounds self-assembling in metastable nanotubes [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…A set of simple guidelines were supplied (see Methods), and in response, a total of 29 pentapeptides were collected. Many literature examples of self-assembling pentapeptides include N-and C-terminii modification (acetylated or carbamidated, respectively) to facilitate assembly [43,44,45,46,47,48]. However, in this work the human-experts were directed to leave the pentapeptide terminii unmodified in alignment with the workflow adopted for the AI-expert.…”
Section: Screening Of Pentapeptidesmentioning
confidence: 99%
“…Interestingly, under identical solution conditions, Fmoc‐(3‐OH)‐ γ Phe self‐assembled into a transient hydrogel which was disrupted over time and finally formed crystalline aggregates ( Figure a). [ 52 ] Absorbance measurement at 405 nm demonstrated the self‐assembly kinetics. Initially, the absorbance decreased due to the formation of a semitransparent temporary hydrogel; however, after 15 min, the absorbance increased and returned to its initial value due to the collapse of the hydrogel and the precipitation of white clusters (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%